2017
DOI: 10.1111/crj.12682
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting fatigue severity in patients with obstructive sleep apnea

Abstract: Our findings indicate that fatigue severity is more likely to be associated with younger age, sleepiness and insomnia, but less likely to be directly related to OSA severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Given that OSA patients have marked sleep impairment, it stands to reason those with CRS may also have a significant reduction in sleep quality, a finding supported by the data in this review. Another study, using the PSQI in those with OSA, demonstrated mean PSQI scores of 8.6, 7.9, and 8.0 for mild, moderate, and severe OSA, respectively 60 . Comparing that study to the data in this review seems to suggest that patients with CRS and NSD appear to have poorer subjective sleep than OSA patients based on the PSQI alone.…”
Section: Discussionmentioning
confidence: 53%
“…Given that OSA patients have marked sleep impairment, it stands to reason those with CRS may also have a significant reduction in sleep quality, a finding supported by the data in this review. Another study, using the PSQI in those with OSA, demonstrated mean PSQI scores of 8.6, 7.9, and 8.0 for mild, moderate, and severe OSA, respectively 60 . Comparing that study to the data in this review seems to suggest that patients with CRS and NSD appear to have poorer subjective sleep than OSA patients based on the PSQI alone.…”
Section: Discussionmentioning
confidence: 53%
“…Fatigue has been found to be associated with obesity, insomnia, and depression, but not with older age in the general population ( Kim et al, 2017 ; Galland-Decker et al, 2019 ). Increased fatigue is seen in several patient groups, such as cancer patients ( Stone et al, 2000 ; Berger et al, 2015 ), multiple sclerosis ( Rooney et al, 2019 ), and Parkinson’s disease ( Stocchi et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased fatigue is seen in several patient groups, such as cancer patients ( Stone et al, 2000 ; Berger et al, 2015 ), multiple sclerosis ( Rooney et al, 2019 ), and Parkinson’s disease ( Stocchi et al, 2014 ). Previous studies have suggested an association between fatigue and OSA ( Hossain et al, 2005 ), but studies have also suggested that fatigue is not related to OSA severity ( Kim et al, 2017 ). Studies have shown that the level of fatigue in OSA is driven by depressive symptoms rather than by OSA severity level, though OSA severity influenced fatigue severity ( Bardwell et al, 2003 , 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…A score of 36 and higher of a maximum of 63 indicates presence of significant or pathologic fatigue. 16 For each patient, relevant demographic, BMI, and medication use including use of anxiolytic and antidepressant medications were collected. The following data were collected from polysomnography (PSG) within the last 3 years: AHI, oxygen desaturation index, respiratory disturbance index, and lowest oxygen saturation.…”
Section: Data Collection Methodsmentioning
confidence: 99%